Biblical concepts and our world - Phillips, Dewi Z. 1934-2006; Von der Ruhr, Mario (Houndsmills, Basingstoke, Hampshire New York Palgrave Macmillan, 2004)
In this collection, distinguished theologians and philosophers of religion explore the relation of key Biblical concepts to our world. They examine a range of concepts, including authority, faith and history, the historical Jesus, the resurrection and miracles.
Includes bibliographical references and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Philosophy -- Congresses; Bible -- Philosophy; Konferenzschrift -- 2002 -- Claremont, Calif